EXPANSION OF LANGUAGE IN THE CENTRAL ANDES AND THE SPHERE OF INTERACTION CHAVIN - Burger, Richard (2014)
This article considers the possibility that the expansion of Aymara was the result of the emergence and growth of the Chavin sphere of interaction during the first millennium BC. Alternatives suggesting that the Aymara expansion could have occurred prior to Chavin during the Late Preceramic (Archaic), the Initial Period (Early Formative) or after Chavin during the Early Intermediate Period are examined and rejected. The recent work of Paul Heggarty and David Beresford-Jones is also explored, particularly their ideas on «strong hypotheses» of language expansion that attempt to link such expansion with forces of history such as conquest, migrations and the spread of intensive agriculture (or staples such as maize). It is suggested that these explanations to not seem to work for the case of Aymara, if this expansion occurred during the Chavin horizon, and an alternative model based on the work of historical linguist Sheldon Pollock on the spread of Sanskrit and the emergence of the Sanskrit cosmopolis is presented.